Antagonistic Regulation of ABA and GA in Metabolism and Signaling Pathways - Liu, Xu; Hou, Xingliang (Frontiers in Plant Science, 2018)
The phytohormones gibberellic acid (GA) and abscisic acid (ABA) are widely recognized as essential endogenous regulators that mostly play antagonistic roles in plant developmental processes and environmental responses. A variety of both internal and external cues oppositely regulate GA and ABA biosynthesis and catabolism, which directly and indirectly affect their signaling pathways and subsequent responses. Recent discoveries have revealed direct molecular links between GA- and ABA-signaling components, which provide novel insights into their antagonistic regulation. In this review, we mainly focus on these recent reports and the growing understanding of GA and ABA antagonism in metabolic regulation and signaling interactions, and attempt to clarify the problems and challenges involved in exploring the complicated regulatory events associated with these two phytohormones.